2011
DOI: 10.1039/c1dt10130g
|View full text |Cite
|
Sign up to set email alerts
|

A facile hydrothermal method to BiSbO4 nanoplates with superior photocatalytic performance for benzene and 4-chlorophenol degradations

Abstract: BiSbO(4) nanoplates with a large BET specific area has been prepared successfully via a facile hydrothermal reaction from Sb(2)O(3) and Bi(NO(3))(3). The effects of reaction conditions and the precursors on the final products were investigated. It is proposed that the redox reaction between Sb(2)O(3) and Bi(NO(3))(3) plays a pivotal role in the formation of nanocrystalline BiSbO(4). The hydrothermally prepared nanocrystalline BiSbO(4) was characterized by X-ray diffraction (XRD), N(2)-sorption BET surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…1 These compounds have been proposed for applications such a photocatalytic degradation of benzene and organic dyes. 2,3 Among them BiSbO 4 is one of the most promising compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These compounds have been proposed for applications such a photocatalytic degradation of benzene and organic dyes. 2,3 Among them BiSbO 4 is one of the most promising compounds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, attempts have been made to determine the electronic band gap, but values ranging from 2.1 to 3.5 eV can be found in the literature. 1,4,7,8 During the last decade, intensive investigations have been carried out on the structural evolution of MTO 4 -type ternary oxides under high-pressure (HP). They showed that compression is an efficient tool to improve the understanding of the main physical properties of vanadates, 9 phosphates, 10 chromates, 11 tungstates, 12 molydbates, 13 arsenates, 14 and many other MTO 4 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This porosity is originated from the inter-particle porosity. As compared with other antimonatebased photocatalysts like Sr 2 Sb 2 O 7 (29.8 m 2 /g) [13] and BiSbO 4 (18.3 m 2 /g) [17] prepared via a similar hydrothermal method, the as-prepared GaSbO 4 shows a very high BET specific surface area of 130.0 m 2 /g. It indicates that the hydrothermal method is an efficient method to prepare nanocrystalline GaSbO 4 with small particle size and large BET specific surface.…”
Section: Resultsmentioning
confidence: 96%
“…Recently we and others have found that some metal oxides consist of central ion of Sb 5+ , like M 2 Sb 2 O 7 (M = Sr 2+ and Ca 2+ ) [12][13][14], PbSb 2 O 6 [15], BiSbO 4 [16,17] and ZnSb 2 O 6 [18] show photocatalytic activity for the degradation of benzene and organic dyes. All these antimonate-based photocatalysts contain distorted Sb O polyhedra and encourage us to explore the photocatalytic performance of other antimonates with distorted Sb O polyhedra.…”
Section: Introductionmentioning
confidence: 99%
“…BiSbO 4 is known as a synthetic phase and has seen use in ceramics and catalysts (Wang et al, 2013;You et al, 2011). Ito et al (1975) grew single crystals of BiSbO 4 up to 1 mm wide and 14 mm long by vapour growth at 900-1200°and noted that the Bi 3+ sites in the crystal could be partially substituted by Sb 3+ in the presence of excess Sb in the synthesis mixtures.…”
Section: Occurrencementioning
confidence: 99%